Kynurenic acid ameliorates lipopolysaccharide-induced endometritis by regulating the GRP35/NF-κB signaling pathway - Wang, Ying; Liu, Zhuoyu; Shen, Peng; Zhao, Caijun; Liu, Bin; Shu, Chang; Hu, Xiaoyu; Fu, Yunhe (Toxicology and applied pharmacology, 2022)
Endometritis is a serious reproductive disease in mammals that commonly results in reproductive loss and even permanent infertility. Kynurenic acid (KYNA) is the main bioactive metabolite of tryptophan degradation and exhibits neuroprotective and anticonvulsant properties. However, little is known about the role of KYNA in achieving endometritis remission. This study investigated the protective effects and mechanisms of KYNA using a mouse model of against lipopolysaccharide (LPS)-induced endometritis. The endometritis model was induced by an intrauterine injection of LPS, and KYNA was intraperitoneally injected before and two hours after LPS treatment. Twenty-four hours after LPS administration, pathological changes in uterine tissues were observed by hematoxylin- and eosin (H&E) staining. The levels of the inflammatory factors, TNF-α and IL-1β, were measured by ELISA. The myeloperoxidase (MPO) activity in uterine tissues was detected using MPO kits and immunohistochemistry. Furthermore, the expression of signaling pathway proteins and tight junction proteins occludin and ZO-1 in uterine tissues was detected by western blot. KYNA prominently inhibited uterine pathological injury and neutrophil infiltration and restricted the secretion of TNF-α and IL-1β in the uteri of subjects with endometritis. Furthermore, KYNA upregulated the levels of the tight junction proteins (TJPs)occludin and ZO-1 in the uterus. In vitro, KYNA inhibited LPS-induced TNF-α and IL-1β production, and NF-κB activation in mouse endometrial epithelial cells (mEECs). In addition, KYNA increased the expression of G protein-coupled receptor 35 (GPR35) and inhibition of GPR35 reversed the anti-inflammatory effects of KYNA. In conclusion, KYNA protected against LPS-induced endometritis by maintaining epithelial barrier permeability and suppressing proinflammatory responses via the GRP35/NF-κB signaling pathway. •Kynurenic acid inhibited the uterus pathological injury and inflammatory cytokines production induced by LPS.•Kynurenic acid up-regulated the levels of the tight junctions proteins occludin and ZO-1.•Kynurenic acid inhibited LPS-induced TNF-α and IL-1β production, NF-κB activation in mouse endothelial cells.•Inhibition of GPR35 reversed the anti-inflammatory effects of kynurenic acid.